Family education and support programme: implementation and cultural adaptation in Cape Verde - Correia, Adriana (2022)
This article describes some preliminary data on the implementation of the Family Education and Support Programme (FAF) on psychosocially at-risk families of Boavista Island, Cape Verde, specifically in relation to its effectiveness in parenting competences. The FAF is a family intervention programme designed to be integrated into preventive and formative actions and it has the purpose of promoting positive parenting and preventing child abuse. This study aims to (a) describe the participants’ psychosocial profile regarding sociodemographic characteristics and negative or risky life events, (b) analyse the effectiveness of the FAF on improving parenting competences, and (c) address the main procedural topics related to the implementation of the FAF in Cape Verde. An experiential and participatory methodology was used with 66 parents, who participated in 12 group sessions, with a weekly periodicity, for four months. The evaluation was performed, in the pre-test and post-test, with the control group and the intervention group. Results show the effectiveness of the FAF in an African context, including its impact. The intervention group improved their post-intervention scores on perceived efficacy and satisfaction with a moderate and high effect size, respectively. We present some recommendations to be considered in future programs to promote positive parenting, since improvements in parents’ competences, are key to reducing neglectful or abusive situations.